YURISDIKSI INTERNATIONAL CRIMINAL COURT (ICC) DALAM PENEGAKAN PELANGGARAN HAK ASASI MANUSIA BERAT OLEH OMAR HASSAN AL-BASHIR DI DARFUR, SUDAN - Mega Oktaviana (Faculty of Law Universitas Sebelas Maret, 2022)
The ICC is independent court that prosecutes serious crimes under article 5 Rome Statue and has jurisdiction of the State Parties. Omar Al-Bashir is alleged of comitting human rights violations in Sudan’s Darfur. However, the problem is that Sudan is not a state party of Rome Statue 1998. The purpose of this research is to find out does the ICC has jurisdiction to investigate and adjudicate human rights violations by Omar Al-Bashir in Darfur, Sudan. This research is prescriptive normative legal research. Type Legal materials include primary and secondary legal materials. The technique of collecting legal materials used is literature study and through research instrument. The results showed that the ICC as an international judicial institution has jurisdiction to investigate and adjudicate human rights violations by Omar Al-Bashir that occurred in Darfur, Sudan. However, Omar Al-Bashir’s status as head of state with immunity, the weak authority of the ICC in carrying out the arrest of Omar Hassan Al-Bashir, and the lack of cooperation between Sudan and state parties in carrying out the arrest of Omar Hassan Al-Bashir hampered the judicial process. The ICC has conducted an investigation, issued a warrant for arrest of Omar Hassan Al-Bashir and cooperated with Sudan so that Sudan agreed to hand Omar Hassan Al-Bashir over to the ICC for trial. The jurisdiction ICC to prosecute Omar Al-Bashir shows that perpetrators of serious human rights violations can still be tried wherever he is regardless their impunity. In addition, international cooperation is necessary in investigation and prosecution of crimes for the smooth of the judicial process.